PENGEMBANGAN FILM DOKUMENTER BERBASIS SETS PADA MATERI PENCEMARAN LINGKUNGAN - Muhammad Badarul Husna; Hairida Hairida; Lukman Hadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThe COVID-19 pandemic has had a negative impact for Indonesia, including the education sector. Teaching and learning activities are using online methods. One of the learning media that can help in the distance learning process is documentary films. The subject matter that can be realized through documentary films is environmental pollution which contains SETS (Science, Environment, Technology, Society) components. This study aims to determine the feasibility level of media and documentary film based on SETS. The form of this research is research and development (R&D) with reference to the ADDIE model which is modified into ADD namely Analysis, Design, and Development. The subject of this research is SETS-based documentary. The data collection instrument used is a media and material feasibility assessment sheet. The results showed the percentage of 94.5% on the feasibility of the media and 97.6% on the feasibility of the material in the very feasible category. In conclusion, this SETSbased documentary is very suitable to be used as a learning medium on environmental pollution material.Keywords: Documentary Film, Environmental Pollution, SETS.